Community Based Study of Rural, Tribal Women Seeking Induced Abortions in a Extremely Low Resource Region - CHHABRA S.; S Jain; K Thool (Journal of Women's Reproductive Health, 2020)
Background Induced abortions are globally sought, whether permitted, or not permitted. Community based information about abortion seeking by rural tribal women is scarce. Objectives Community based study was carried out to know the magnitude, profile, reasons, places, persons performing IA for rural tribal women. Material Methods Study was conducted in 118 villages to get the study subjects . Women from every fourth house were interviewed for desired information. Results and Conclusion Of all abortions, 2.17% in Melghat and 24.38 %in Sewagram were IA. Most women who had IA were young and 19% in Melghat region, 2.6% in Sewagram region were illiterate. Majority of Sewagram region, were housewives of low middle class, in Melghat unskilled workers of low economic class. In Melghat region all women reported seeking IA at health facilities,63% Private hospitals (PH), 18.5% Sub centres (SC), 7.4% Medical College (MC), 7.4% District hospital(DH), 3.7% Primary Health Centres (PHCs) and In Sewagram region 58% PH, 23% MC, 6.7% PHCs, 3.9% DH, 3.9% SCs and 3.9% at home. Most women said they had IA for spacing with no contraceptive use or contraceptive failure, poor health, poverty, IA were done medically in 76.2%, surgically 23%. No sex–selective IA were reported and there was no evidence Many women lacked awareness and had misconceptions, more so in Melghat region. In focus group discussions, common reasons for disfavoring IA were personal beliefs (34%), practice restrictions (19%). There was extreme poverty, still PH were used. Lot of awareness is required.
Keywords: Rural Tribal Women